AGE-RELATED VARIATIONS IN ALCOHOLIC LIVER CIRRHOSIS - Koshimuratova Manzura Ongarbay qizi (GLOBAL SCIENTIFIC RESEARCH AND INTELLECTUAL PURSUITS, 2025)
Age-related variations in alcoholic liver cirrhosis represent a critical intersection of physiological aging processes and chronic alcohol exposure, leading to heightened susceptibility, accelerated disease progression, and poorer outcomes across different age groups. This review synthesizes recent evidence from high-impact studies, highlighting metabolic alterations, increased hepatic vulnerability in the elderly, and emerging trends of rising incidence and severity in younger populations. Key findings indicate diminished enzyme activity and reduced water distribution volume with aging, exacerbating ethanol toxicity, while younger adults show alarming hospitalization and mortality increases due to behavioral factors. The analysis underscores the need for age-specific interventions to mitigate the global burden of alcoholic liver disease (ALD).